Disability Services in Dual Enrollment - Benjamin A. Schoenkin (Washington University Journal of Law & Policy, 2021)
An increasing number of secondary students are taking dual enrollment courses. What does this mean for secondary students with disabilities when there are differences among the laws that apply to students with disabilities at the secondary and college levels? This Note looks at the following question: In dual enrollment classes, are secondary schools required to provide an IDEA or Section 504 FAPE (and the accompanying disability services) to students with disabilities or can the secondary school rely on the disability services that the community college provides to college students? Schoenkin’s legal analysis finds that secondary schools are required to provide an IDEA or Section 504 FAPE (and the accompanying disability services) to students with disabilities in dual enrollment courses. Schoenkin proposes a plan for secondary schools and colleges based on this conclusion.
Keywords: disability; dual enrollment; secondary school; IDEA; Individuals with Disabilities Education Act; Section 504; Section 504 of the Rehabilitation Act of 1973; free appropriate public education; FAPE; Section 504 FAPE; Individualized Education Program; IEP